2020
DOI: 10.3390/genes12010019
|View full text |Cite
|
Sign up to set email alerts
|

Structural Variability, Expression Profile, and Pharmacogenetic Properties of TMPRSS2 Gene as a Potential Target for COVID-19 Therapy

Abstract: The human serine protease serine 2 TMPRSS2 is involved in the priming of proteins of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and represents a possible target for COVID-19 therapy. The TMPRSS2 gene may be co-expressed with SARS-CoV-2 cell receptor genes angiotensin-converting enzyme 2 (ACE2) and Basigin (BSG), but only TMPRSS2 demonstrates tissue-specific expression in alveolar cells according to single-cell RNA sequencing data. Our analysis of the structural variability of the TMPRSS2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Since May 2020, when we reported the TMPRSS2 variant rs12329760 as possibly damaging to protein structure/function and raised the possibility that it could partly explain host susceptibility to COVID-19 severity [65] , several other studies have also supported this hypothesis [66] , [67] , [68] , [69] , [70] , [71] . In this study we have confirmed our initial hypothesis and provided a mechanistic effect to explain how this variant may contribute to the host susceptibility to severe COVID-19.…”
Section: Discussionmentioning
confidence: 94%
“…Since May 2020, when we reported the TMPRSS2 variant rs12329760 as possibly damaging to protein structure/function and raised the possibility that it could partly explain host susceptibility to COVID-19 severity [65] , several other studies have also supported this hypothesis [66] , [67] , [68] , [69] , [70] , [71] . In this study we have confirmed our initial hypothesis and provided a mechanistic effect to explain how this variant may contribute to the host susceptibility to severe COVID-19.…”
Section: Discussionmentioning
confidence: 94%
“…Regarding the Futura 75 variety, the inhibition of Bcl-2 and TGFβ was statistically significant at all tested concentrations, whereas the EOs of the other two cultivars did not significantly alter Bcl-2 and TGFβ gene expression. Recent studies explored the potential of industrial hemp polar extracts as anti-COVID-19 agents, with particular regards to the gene expression inhibition of ACE2 and TMPRSS2 [12,13], which, besides being co-expressed [33], are reputed to play master roles in mediating SARS-CoV-2 virus entry in the human host [15,16]. This is as also summarized by the pathway map hsa05171 deposited on the KEGG PATHWAY Database (https://www.genome.jp/kegg/pathway.html).…”
Section: Resultsmentioning
confidence: 99%
“…The antiviral activities of Glycyrrhizin have been extensively studied in the context of other human viruses and most notably, the drug was found to potently suppress replication of two clinical isolates of SARS-associated coronavirus in Vero cells ( Cinatl et al, 2003 ), and preliminarily, neutralize SARS-CoV-2 by inhibiting the viral main protease ( van de Sand et al, 2021 ). Further, Carvedilol and Acetaminophen have been reported to decrease the expression of ACE2 and serine protease TMPRSS2, respectively ( Zarubin et al, 2020 ; Skayem and Ayoub, 2020 ), both of which are required for SARS-CoV-2 entry into cells ( Hoffmann et al, 2020 ). Hence, drug combinations that simultaneously exert both anti-inflammatory and antiviral effects against SARS-CoV-2 may have the greatest potential to be effective in treating COVID-19.…”
Section: Discussionmentioning
confidence: 99%